Pertumbuhan Awal Tanaman Penyusun Agroforestri Sengon (Falcataria mollucana)+Manglid (Magnolia champaca)-Rumput Pakan Ternak pada Umur Sembilan Bulan - Aditya Hani; Levina Pieter Geraldine (Jurnal Ilmu Pertanian Indonesia, 2019)
Vegetative soil and water conservation can be done by planting annual plants (timber) and crops. On sloping areas, terraces function to prevent erosion and to maintain the soil fertility. One effort to protect the terrace is to plant animal-feed plants. The combination of woody plants and grasses can increase the value of conservation and provide results for landowners, namely wood and forage. The research was designed to evaluate the growth of manglid (Magnolia champaca), sengon (Falcataria mollucana), and elephant grass (Pennisetum purpureum) planted in agroforestry. The study used a split plot design group with wood plant species, namely 4 spacing (3 x 3; 3 x 4; 3 x 5; and 3 x 6 m) each of three replications. The number of staple plants per treatment of 49 plants (7 x 7) by means of the type of sengon and manglid was planted by alternating hose. Elephant grass was planted along the terrace with a spacing of 1 x 1 m. The results showed that the spacing of the main plants 3 x 5 m with a distance between 5 m lines gave the best tree growth (diameter 24.5 mm and height 129.41 cm). The number of shoots per elephant grass clump ranged between 44-134 shoots with a wet weight per sample range of 83.6-278/g/shoot, while the productivity per area of 4 m2 ranged between 0.8-13.25 kg wet weight and 0.32-5.26 kg dry weight.